Barriers to access for severe acute malnutrition treatment services in Pakistan and Ethiopia: a comparative qualitative analysis. Issue 10 (13th November 2014) - Puett, Chloe; Guerrero, Saul
Abstract: Objective: To understand and compare the primary barriers households face when accessing treatment for cases of childhood severe acute malnutrition (SAM) in different cultural settings with different types of implementing agencies. Design: The study presents a comparative qualitative analysis of two SAM treatment services, selected to include: (i) one programme implemented by a non-governmental organization and one by a Ministry of Health; and (ii) programmes considered to be successful, defined as either coverage level achieved or extent of integration within government infrastructure. Results from individual interviews and group discussions were recorded and analysed for themes in barriers to access. Setting: Sindh Province, Pakistan; Tigray Region, Ethiopia. Subjects: Beneficiary communities and staff of SAM treatment services in two countries. Results: Common barriers were related to distance, high opportunity costs, knowledge of services, knowledge of malnutrition and child's refusal of ready-to-use foods. While community sensitization mechanisms were generally strong in these well-performing programmes, in remote areas with less programme exposure, beneficiaries experienced barriers to remaining in the programme until their children recovered. Conclusions: Households experienced a number of barriers when accessing SAM treatment services. Integration of SAM treatment with other community-based interventions, as the UN recommends, can improve access to life-saving services. Efforts to integrate SAM treatment into national health systems should not neglect the community component of health systems and dedicated funding for the community component is needed to ensure access. Further research and policy efforts should investigate feasible mechanisms to effectively reduce barriers to access and ensure equitable service delivery.